Preparation and characterization of chitosan/whey isolate protein active film containing TiO2 and white pepper essential oil - Wang, Ying; Wang, Ji; Lai, Jing; Zhang, Xin; Wang, Yongliang; Zhu, Yingchun (Frontiers in Nutrition, 2022)
This study comprehensively evaluated the properties of the bio-composite films prepared from chitosan (CS) and whey isolate protein (WPI) by incorporating nano-TiO2 and white pepper essential oil (WPEO) as functional components. The prepared films were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM), and the effects of TiO2 and WPEO on the physicomechanical properties, barrier performance, antioxidative capacity, and antibacterial properties of films were also investigated. The results showed that hydrophobicity, mechanical properties, and UV-barrier properties of composite films were significantly improved by incorporating nano-TiO2 and WPEO. The FTIR results showed excellent interactions between TiO2 and WPEO with CS/WPI compound, and the SEM results indicated a good dispersion of TiO2 into the composite films. The antioxidative and antibacterial properties of films were significantly enhanced by incorporating WPEO. Overall, the bio-nanocomposite films developed by incorporating TiO2 and WPEO exhibits a promising application in food packaging.